Understanding consumer sensory perception of beer and wine body - Ivanova, Natalja (2023)
Changes in consumer preferences, health concerns associated with excessive alcohol consumption, governmental policies and environmental conditions have driven research efforts towards exploring and producing alcoholic beverages with reduced alcohol content, namely beer and wine. A highly desirable and widely accepted mouthfeel attribute in beer and wine with lower alcohol – body, is important for consumer appreciation, willingness to buy, and overall acceptance of beverages. Nevertheless, to date, the concept is ill-defined. With lower alcohol products described as imbalanced and thin, the development of beverages with high consumer acceptability is required. Research indicates there is growth in the volume of lower alcohol wines and beers being exported, thereby emphasising the importance of meeting market demand and emerging opportunities guided by the consumer.